0743 The Pharmacokinetic Adverse Event Relationship for FT218, a Once-Nightly Sodium Oxybate Formulation. (27th May 2020) - Seiden, D; Grassot, J; Monteith, D; Dubow, J
Abstract: Introduction: Sodium oxybate is an effective treatment for excessive daytime sleepiness and cataplexy in patients with narcolepsy. The approved formulation requires twice-nightly dosing: at bedtime and 2.5 - 4 hours later, which results in two distinct Cmax's. FT218 is a controlled-release formulation of sodium oxybate intended for once-nightly dosing, using Avadel's proprietary Micropump™ technology. The objective of this study was to evaluate the pharmacokinetic-adverse event (AE) relationship for FT218, an investigational once-nightly sodium oxybate formulation. Methods: Six single-dose, randomized, crossover studies that assessed the pharmacokinetics of FT218 at 4.5, 6, 7.5 and 9 g in healthy voluntters were used in this analysis. Lattice plots, "spaghetti" plots, and scatter plots of individual gamma hydroxybutyrate concentrations and indicators when AEs by system, organ, or class (SOC) were created to determine any PK-AE relationship. Results: A total of 129 healthy volunteers received single doses of FT218 between 4.5 - 9 g. Most AEs, specifically for the neurological and gastrointestinal SOC, occurred close to Tmax, during the Cmax period, which for FT218 was around 1.5-2 hours after dosing. These AEs were known AEs associated with sodium oxbyate. There appeared to be no clear correlation between individual plasma GHB concentrations levels and AEs between subjects. Individual AEs were equally distributed above and below the mean population Cmax and AUCinf for the dataset. Conclusion: In general, adverse events for FT218 occurred around Tmax . There was no clear population toxicokinetic range for when AEs occur with FT218, but mostly individual thresholds. Since it appears AEs are related to Cmax, and FT218 only has one Cmax compared to two with the currently available product, it is hypothesized that FT218 will have a favorable safety profile compared to twice-nightly dosing. Support: This work was supported by Avadel Pharmaceuticals